Peran PT. Permodalan Nasional Madani Mekaar Dalam Pembiayaan Usaha Mikro Kecil Menengah (UMKM) Di Kota Jambi - Erlin Alhamrani; Youdhi Prayogo; Nurrahma Sari Putri (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Limited capital is one of the reasons people do not dare to open a business, because for an entrepreneur, capital is one of the requirements for running or building a business. There are two forms of capital, the first is capital in the form of money or goods. Second, namely intellectual capital such as knowledge, abilities, skills and commitment. The distribution of productive capital is expected to be able to improve the community's economy with business capital loans for the community. In reality, there are many negative perceptions regarding business capital lending, so it is canceled. The formulation of the problem in this research is the Role and Constraints/Barriers of PT Permodalan Nasional Madani Mekar in Financing Micro, Small and Medium Enterprises (MSMEs) in Jambi City. The research method in this research is a qualitative research method. The data collection techniques were carried out using observation, interviews and documentation. The results of this research are that the role of PT Permodalan Nasional Madani Mekaar in financing is to help MSME players face their obstacles in running MSMEs such as lack of capital. PT Permodalan Nasional Madani Mekaar provides capital assistance with a very fast process and without any burdensome requirements for its customers. And the obstacles/obstacles faced by PT Permodalan Nasional Madani Mekaar include the factor of customer dishonesty during interviews with PNM Mekaar and obstacles to customers running away or abandoning responsibilities.